ITSBAT TALAK: MENEGOSIASIKAN KEPASTIAN HUKUM ISLAM DAN PERLINDUNGAN HAK PEREMPUAN - Fuat Hasanudin (Sahaja: Journal Sharia and Humanities, 2024)
This research aims to analyze the issue of divorce outside the court and negotiate between the certainty of Islamic law and the protection of women's rights. Divorce outside of court is still a common practice in Indonesia, even though this is contrary to positive law provisions which require divorce to be carried out before a court hearing. The research method used is a literature study by analyzing various references related to a normative approach. The research results show that divorce outside of court is considered valid according to Islamic law, but is not valid according to positive law in Indonesia. This creates legal uncertainty and potential violations of women's rights, especially regarding the right to iddah living, joint property, and the right to remarry. On the one hand, divorce before the court is part of efforts to enforce legal certainty in divorce, but on the other hand, the practice of divorce outside the court has various potential violations of women's rights. Itsbat Talak is an effort to negotiate between the certainty of Islamic law and strengthening legal protection for women in the practice of divorce